An e-learning platform for managing seafarers’ health issues on board: pilot use on the Greek shipping industry - Zerva, Kanella; Drylli, Aikaterini; Chrysovergis, Aristeidis; Chrysovitsiotis, Georgios; Kyrodimos, Efthymios (International Journal Of Community Medicine And Public Health, 2022)
Background: It is well known that health management on board is a major challenge for maritime authorities, shipping companies, and seafarers. This paper presents the outcomes of the pilot use of an e-learning platform for dealing with mariners’ health issues aboard. Methods: The survey took place in the Piraeus port (Attica, Greece) during November 2021-February 2022. Data were gathered from merchant ship mariners (n=41) by questionnaires at the Piraeus port, Athens, Greece. A descriptive statistical analysis was performed by the SPSS v23.0® and Microsoft excel© 365. Results: Twenty-one seafarers (51.21%) were at the age group 31-40 years old, fifteen (36.58%) were at the age group 41-50 years old, four (9.75%) were at the age group 51-60 years old and 1 participant (2.43%) was over 60 years old. Twenty-six (63.41%) of the participants were occupied on deck department while fifteen (36.58%) in the engine room. A statistically significant higher score on web-test after the use of SeaHealth platform was confirmed by paired t test (p<0.001) (Figure 3). Conclusions: The participants who used the e-learning platform improved their knowledge on first aid, increased their basic skills on medical care, and achieved more confidence in handling emergencies effectively aboard.